2020
DOI: 10.3389/fmed.2020.557044
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence, Risk Factors and In-Hospital Mortality of Acute Kidney Injury in Patients After Surgery for Acute Type A Aortic Dissection: A Single-Center Retrospective Analysis of 335 Patients

Abstract: Background: Acute kidney injury (AKI) is a common complication of cardiac surgery, which could lead to increased morbidity and mortality. Acute type A aortic dissection (AAAD) is a life-threatening cardiac disease and can be closely related to post-operative AKI. However, data on the incidence of AKI defined by the newest Kidney Disease: Improving Global Outcomes (KDIGO) criteria and in-hospital mortality of a homogeneous population who underwent AAAD are limited. We aimed to investigate the incidence of AKI d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
31
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 39 publications
(53 reference statements)
6
31
3
Order By: Relevance
“…The CPB duration in the majority of patients was 3–4 h, and the possibility of POHL increased a lot due to the very long CPB time. However, it was similar to the results of AADS-related studies at home and abroad [ 24 , 25 ]. This may be attributed to the complexity and difficulty of the AADS, which implies a possibility of higher postoperative lactate levels and increased incidence of POHL than other cardiac operations and thus higher mortality.…”
Section: Discussionsupporting
confidence: 87%
“…The CPB duration in the majority of patients was 3–4 h, and the possibility of POHL increased a lot due to the very long CPB time. However, it was similar to the results of AADS-related studies at home and abroad [ 24 , 25 ]. This may be attributed to the complexity and difficulty of the AADS, which implies a possibility of higher postoperative lactate levels and increased incidence of POHL than other cardiac operations and thus higher mortality.…”
Section: Discussionsupporting
confidence: 87%
“…AKI is a common complication after aortic surgery which is more likely associated with high mortality. In present study, we observed that 23 patients presented AKI and five patients required continuous renal replacement therapy because of renal failure after operation, which is in accordance with the results reported by Li et al ( 35 ). Open total aortic arch replacement is a complicated operation that includes the application of hypothermic circulatory arrest which can potentially lead to severe renal ischemic-reperfusion injury.…”
Section: Discussionsupporting
confidence: 93%
“…This means that the risk of renal tubular injury can be minimized by avoiding deep hypothermia and decreasing the CPB duration. Other risk factors of developing AKI underwent aortic arch surgery, which did have been found were older age, obesity, preoperative hypertension, chronic renal disease, emergency surgery, a higher number of red blood cell transfusion, and renal malperfusion due to the dissection itself or cardiac tamponade (35,36,39). As a result, emergency aortic surgery was strongly related to the development of postoperative AKI and might be known as a risk factor for AKI.…”
Section: Discussionmentioning
confidence: 96%
“…Received more blood transfusion and blood loss increase the bilirubin level, and they are risk factors of HB following cardiac surgery [5]. Moreover, CPB time, cross-clamp time, received more blood transfusion and blood loss were also associated with AKI after cardiac surgery with CPB [19,20]. The similar risk factors of HB and AKI may explain the positive impact of HB on AKI and the poor outcomes of HB-AKI group in our study.…”
Section: Discussionsupporting
confidence: 56%